Life Cycle Assessment of Urban Passenger Transportation - John Samuel, Dr. Immanuel (Journal of Science & Technology, 2024)
This paper describes a life-cycle analysis (LCA) performed for urban passenger transport (cars and urban buses) in United States for the years 2015–2050 in five-year steps. It is assumed that the only change made is the propulsion technology/fuel used and that the distance driven by all vehicles (within each mode) per year remains the same. The complete conversion to a single powertrain type is neither realistic or necessarily desirable, but the intention of this LCA is not to provide a forecast of greenhouse gas (GHG) and air pollution emissions or other factors; the system is too complex with more uncertainties. Instead, the intention is to compare the effect of applying the various technologies/fuels in order to discern their effect in a simplified manner and identify any possible limitations and allow further discussions on the ideal policy strategy.
Keywords: Life-cycle analysis; Urban passenger transport; Greenhouse gas; Urbanization